Glycine and Melatonin Improve Preimplantation Development of Porcine Oocytes Vitrified at the Germinal Vesicle Stage - Tang, Yu; Zhang, Ying; Liu, Lixiang; Yang, Yifeng; Wang, Yan; Xu, Baozeng (Frontiers in Cell and Developmental Biology, 2022)
Lipid-rich porcine oocytes are extremely sensitive to cryopreservation compared to other low-lipid oocytes. Vitrification has outperformed slowing freezing in oocyte cryopreservation and is expected to improve further by minimizing cellular osmotic and/or oxidative stresses. In this study, we compared the effects of loading porcine cumulus-oocyte complexes with glycine (an organic penetrant) or glycine plus melatonin (an endogenous osmotic agent) during vitrification, thawing and subsequent maturation to mitigate osmotic injuries or osmotic and oxidative damages on the developmental potential of porcine oocytes. Our data demonstrated that glycine treatment significantly increased the vitrification efficiency of porcine oocytes to levels comparable to those observed with glycine plus melatonin treatment. It was manifested as the thawed oocyte viability, oocyte nuclear maturation, contents of reactive oxygen species, translocation of cortical granules and apoptotic occurrence in mature oocytes, levels of ATP and transcripts of glycolytic genes in cumulus cells (markers of oocyte quality), oocyte fertilization and blastocyst development. However, the latter was more likely than the former to increase ATP contents and normal mitochondrial distribution in mature oocytes. Taken together, our results suggest that mitigating osmotic and oxidative stresses induced by vitrification and thawing can further enhance the developmental competency of vitrified porcine oocytes at the germinal vesicle stage.